Assessment of Oral Stereognosis and Denture Satisfaction in Old Denture Wearers: A Retrospective Study - Hina Memon; Muhammad Rizwan Memon; Naveed Memon; Lubna Memon (Gandhara University, 2023)
OBJECTIVES Stereognosis has been investigated occasionally to predict the prognosis of treatment with complete dentures. This study evaluated oral stereognosis and satisfaction levels in completely edentate patients wearing prostheses for at least three months. METHODOLOGY From November 2014 and January 2016, data from 322 patients' follow-up visits were collected from records of the Prosthodontics department at Liaquat University of Medical and Health Sciences, Jamshoro. Denture satisfaction was assessed using a self-structured proforma, and oral stereognosis was measured using different-shaped objects made from self-cure acrylic resin, kept in the oral cavity without showing them to the patient. The frequency of qualitative variables was determined for data analysis, and a chi-square test was applied. Significant P-values were defined as those less than 0. RESULTS The male-to-female ratio was 1.2:1, with 50.9% wearing a prosthesis for less than a year and the minimum range being 3-6 years (13.66 %). Only 31 had stereognosis positive but were completely satisfied with their prosthesis, while 85 who were unsatisfied were found to have positive sensory perception. Statistical analysis for all groups shows a p-value of 0.000 for patient satisfaction with denture wear which is statistically significant. Most patients with the least duration of wear found their stereognosis positive and were unsatisfied with the prosthesis and vice versa. The chi-square test shows a statistically significant value for both groups of stereognosis i-e 0.0001.. CONCLUSION Patients with the shortest period of wear were found to be more dissatisfied, but their oral perception remained intact, while those with more experience complained less but had reduced stereognosis.